Fermionic Greybody Factors in Schwarzschild Acoustic Black Holes - Kanzi, Sara; Sakalli, Izzet (Mdpi, 2023)
In Schwarzschild acoustic black hole (SABH) spacetime, we investigate the wave dynamics for the fermions. To this end, we first take into account the Dirac equation in the SABH by employing a null tetrad in the Newman-Penrose (NP) formalism. Then, we consider the Dirac and Rarita-Schwinger equations, respectively. The field equations are reduced to sets of radial and angular equations. By using the analytical solution of the angular equation set, we decouple the radial wave equations and obtain the one-dimensional Schrodinger-like wave equations with their effective potentials. The obtained effective potentials are graphically depicted and analyzed. Finally, we investigate the fermionic greybody factors (GFs) radiated by the SABH spacetime. A thorough investigation is conducted into how the acoustic tuning parameter affects the GFs of the SABH spacetime. Both the semi-analytic WKB method and bounds for the GFs are used to produce the results, which are shown graphically and discussed.
Keywords: acoustic black holes; greybody factors; fermions; Dirac equation; Rarita-Schwinger equation; Hawking radiation